Cross-sectional assessment of Angiostrongylus cantonensis transmission risk mediated by invasive apple snails in Jiangsu province of China - Zhang, Qiang; Mao, Fanzhen; Ni, Bixian; Zhang, Jiayao; Tang, Feng; Gong, Xinyi; Liu, Yaobao (PLOS Neglected Tropical Diseases, 2025)
Background Angiostrongylus cantonensis, a zoonotic nematode responsible for eosinophilic meningitis, is acquired in China principally through ingestion of raw or under-cooked invasive apple snails—the vector implicated in almost all Chinese outbreaks to date. Despite the widespread distribution of these snails in Jiangsu Province of China, systematic assessments of infection risks and public awareness remain limited. Methodology/Principle findings We carried out a cross-sectional study in six prefectural-level cities in Jiangsu. In total, 732 wild apple snails were collected from different habitats and screened for A. cantonensis larvae by pepsin–HCl digestion and microscopy. 74 local farmers markets were inspected for the sale of live or processed apple snails. Simultaneously, a validated Knowledge, Attitudes, and Practices (KAP) questionnaire was conducted with 630 randomly selected residents. Data analysis employed SPSS for descriptive statistics and multivariate linear regression was used to identify predictors of higher scores. All wild-caught snails tested negative for A. cantonensis, and no apple snails were found for sale in any market. Overall, the public demonstrated a high level of knowledge and positive attitudes towards the risks posed by apple snails; however, gaps in practice were evident: 40.3% of respondents reported not separating utensils used for raw foods from those used for cooked foods, and 78.7% reported snail sightings to authorities, while only 22.1% had ever used the Apple Snail Inspector (ASI) mini-program. KAP scores differed significantly among different demographic groups. Multivariable linear regression analysis revealed that age, city of residence, and education level were significant predictors of KAP scores. Conclusion/Significance While no infected snails were detected in this study, the potential risk of transmission remains because of the widespread presence of competent apple snails. Targeted health education programs that address behavioral gaps among older and less-educated residents could further minimize the threat of A. cantonensis introduction and safeguard both public health and ecological security.